The physics of oscillate boiling - Nguyen, Dang Minh (Nanyang Technological University, 2019)
The boiling crisis is widely known as the greatest challenge that limits the working capacity of nucleate boiling. This phenomenon takes place when excessive heat supply creates a vapor film, separating the boiling liquid from the heating substrate. This results in the drop of heat transfer efficiency and a significant rise of the device’s temperature. Our work introduces a new regime called oscillate boiling, in which by confining the heat source, the boiling bubble oscillates stably for millions of cycles instead of growing. This mechanism eliminate the possible formation of the vapor film and might be the solution for the boiling crisis. The thesis begins with the first experimental observations where the phenomenon is characterized with high speed imaging, acoustic emission and thermal readings of the heating substrate. We then explain the oscillatory behavior of the boiling bubble with two mechanisms: the liquid jet created by the bubble’s non-spherical collapse, and the thermal kick upon the jet’s impact onto the heating substrate. The explanation is supported with numerical simulation on the bubble dynamics and the flow profile of the surrounding liquid. The following works focus on bringing oscillate boiling towards application, which begins with moving from an laser-based heater to an electrical heater, which allows easier setup, higher energy efficiency and much better controls. Along this way we discover two different mode of oscillate boiling, namely unstable oscillate boiling, associated with low heating power, where the bubble oscillates shortly for only a few milliseconds and starts growing, and stable oscillate boiling, associated with high heating power, where the bubble oscillates stably with a fixed maximum radius. Finally, we present two potential application of oscillate boiling. Firstly, by performing experiments on parabolic flights, we show that unlike nucleate boiling which depends heavily on gravity, oscillate boiling’s functionality remains intact regardless of the gravity condition. Secondly, we study the interaction of two closely-placed oscillate boiling bubbles and discover that depending on their distance and heating power, the two bubbles can either quickly merge, oscillate independently, or most interestingly, synchronize. This results provide the design criteria to number-up the oscillate boiling phenomenon to commercializable scale.